Editorial Introduction: Special Issue: Time, Urgency, and Collaboration in the Corporate University - El-Tayeb, Fatima; Stehle, Maria (Feminist formations, 2022)
Elite universities saw huge gains on their endowments while community colleges are struggling to survive4 and lipservice to "diversity" does not translate into job security.5 We began this work with the conviction that transnational, intersectional collaborative strategies are urgently needed in response to the global rise of neo-nationalism within a persistent system of neoliberal racial capitalism: violence, poverty and displacement are escalating while wealth disparities continue to increase. Productivity translates into numbers and speed, resources are distributed based on seemingly neutral algorithms, while teaching and scholarship are assessed in terms of numerically measurable outcomes. [...]while right wing movements frame academia as a hub of subversive, radical thinking and activism, innovation and collaboration in the service of transformation often face institutional obstacles. The emphasis in the essays in this volume is not just on identifying injustice and violence but on creating paths for alternatives to emerge, to, with cover artist Althea Murphy-Price, position anew, create new spaces and paces, new materials, notions of beauty, and forms of resistance, to build communities and collaborations that will "imagine otherwise" (Sharpe 2006, 115)7 and make different collaborations and worlds possible. On Our Cover Art Althea Murphy-Price received her B.A. in Fine Art from Spelman College before completing her Master of Arts in Printmaking and Painting at Purdue University and her Master of Fine Arts at Tyler School of Art, Temple University.